Congenital hepatoblastoma in a neonate - Shanbhag, Manas Maruti; Rao, Subba (International Journal of Contemporary Pediatrics, 2018)
Hepatoblastoma is a rare cause of mass abdomen and distension of abdomen in neonates. In this report, a 1-day-old baby who presented with abdominal distension at birth is being described for its unusual presentation. Diagnosis of hepatoblastoma in the antenatal period is possible with the available imaging modalities such as ultrasound abdomen. Caesarean section is recommended when HBL is antenatally diagnosed as vaginal delivery may cause tumor rupture. Beckwith-Wiedemann syndrome, hemihypertrophy and low birth weight are common associations of HBL. Serum Alpha feto protein (AFP) is the most useful laboratory test for hepatoblastoma and hepatocellular carcinoma. AFP is produced in the fetal liver and yolk sac, and levels decline to adult values during the first 6 months after birth. AFP can be used as a tumour marker for screening and confirmation of diagnosis though it is not a very specific tumour marker. Hepatoblastoma should be considered in the differential diagnosis when a neonate presents with distension of abdomen.